Ovothiol-A Exhibited Protective and Therapeutic Effect against Hyperthyroidism in Rats - Gaber, Rahma; Aziz Baiomy, Ahmed Abdel; Mohamed, Ayman Saber (Current Topics in Medicinal Chemistry, 2025)
Introduction2.5% of adults worldwide suffer from hyperthyroidism, which is associated with osteoporosis, heart disease, and increased mortality.AimThe current study evaluates the protective and therapeutic effect of Ovothiol A on Thyroxine-induced hyperthyroidism in rats.MethodsExperimental animals were split into two categories: protective and curative. Each group was further separated into three subgroups (6 per group): control, hyperthyroidism (HT), and Ovothiol-A (250 mg/kg). Thyroxine hormone (600 mg/kg) is administered orally to rats to induce HT.ResultsOvothiol-A supplementation resulted in significant decreases in organ weight index, T3, T3,T4, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, malondialdehyde, nitric oxide levels, and tumour necrosis factor-alpha while increasing in body weight, TSH, glutathione reduced, catalase, and glutathione-S-transferase levels. Histopathological investigation revealed significant thyroid and liver tissue improvements, significantly reducing collagen deposition.ConclusionOvothiol-A exhibited protective and therapeutic effects against hyperthyroidism in rats. Ovothiol-A exhibits antithyroid activity by stimulating the antioxidant system, reducing inflammation, and restoring thyroid hormone levels.
Keywords: oxidative stress